The Role of Practicing Strategic Entrepreneurship in transformation Towards Smart Organizations: A Field Study on Palestinian Information Technology Companies - Abu Ghaben, Nedal Farouq; Bakri, Ibrahem Subhi; Abu Ghaben, Ahmed Farouq (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to explore the nature of the relationship between practicing strategic entrepreneurship and the transition toward smart organizations, and to demonstrate the impact of practicing strategic entrepreneurship on the transition toward smart organizations. The study population consisted of employees in supervisory positions, including department managers, unit heads, and section heads of IT companies, totaling 62 companies. The study concluded with several findings, including that the level of practicing strategic entrepreneurship in Palestinian IT companies was high, with a relative weight of 75.3%. Additionally, the level of availability of smart organizations in Palestinian IT companies was high, with a relative weight of 73%. It was found that there is a strong positive correlation with statistical significance at the significance level (α≤ 0.05) between practicing strategic entrepreneurship and the transition toward smart organizations, with a correlation coefficient of 0.890."
Keywords: Strategic Entrepreneurship; Smart Organizations; Information Technology